The Influence of Employee Empowerment on Goal Orientation Through Work Accuracy - Fachrudy Asj’ari; Bisma Arianto; Yanus Sumitro; Milla Cendy Audia; Aristyanto, Erwan (International Journal of Economics, Commerce, and Management, 2026)
The research aims to find out and lyze the influence of employee empowerment on goal orientation through work accurancy at the Gempolkrep Sugar Factory, Gedeg district, Mojokerto Regency. The research method used is a quantitative research method with the number of samples used as many as 117 respondents using probability sampling techniques with proportionate random sampling techniques. The method used in the collection of data this study is to use a questionaire method with a scale os assesment using the likert scale. The data analysis technique used in this study is using SEM (stuctural equation modeling) with analysis test tools using IBM SPSS AMOS Statistics Version 22 software. The results showed that : 1) Employee empowerment has a significant and positive effect on the work accurancy of the Gempolkrep Sugar Factory in Mojokerto Regency. 2) Eployee empowerment has an significant and negative effect on the goal orientation of the Gempolkrep Sugar Factory in Mojokerto Regency. 3) Work accurancy has an significant and positive effect on the goal orientation of the Gempolkrep Sugar Factory in Mojokerto Regency.